Anaplastic Lymphoma Kinase (ALK)-positive Tumors: Clinical, Radiographic and Molecular Profiles, and Uncommon Sites of Metastases in Patients With Lung Adenocarcinoma. (April 2019) - Gupta, Rohan; Amanam, Idoroenyi; Rahmanuddin, Syed; Mambetsariev, Isa; Wang, Yingyu; Huang, Charity; Reckamp, Karen; Vora, Lalit; Salgia, Ravi
Abstract : Introduction: Anaplastic lymphoma kinase ( ALK) gene rearrangements are observed in about 4% to 8% non–small cell lung cancer (NSCLC). ALK + tumors have been associated with increased pleural and pericardial disease. Our primary objective was to determine the uncommon sites of metastasis of ALK + NSCLC. Secondary objectives included study of coexisting mutations and factors impacting survival of ALK + NSCLC. Methods: All patients with metastatic ALK + NSCLC at the City of Hope Cancer Center in Duarte, California from 2010 to 2017 were selected for retrospective chart review. The demographic variables were collected. The molecular statuses of patients were evaluated through commercially available platforms for next-generation sequencing. Three-dimensional volumetric images were generated for the primary lesion and different sites of metastasis. Results: Sixty two patients with ALK + NSCLC were identified from 2010 to 2017. The median age was 59 with 36 (58%) female individuals and only 20 (32%) smokers. Twenty four patients had uncommon sites of metastasis which were thyroid, soft tissue, chest and abdominal wall, spleen, peritoneum, omentum, kidney, and ovary. Common characteristics of the primary lesions were right upper lobe location (N=23 [37%]), oval shape (N=22 [35%]), irregular margins (N=26 [42%]), solid lesions (N=27 [44%]), presence of pleural contact or effusion (N=22 [35%]). Twenty four patients had next-generation sequencing testing which showed coexisting mutations such as TP53 (N=8), EGFR (N=5), KRAS (N=3). Patients with uncommon sites of metastasis had a decreased median survival compared with common sites (39 vs. 82 m, P =0.046). Conclusion: In NSCLC, ALK rearrangements may not be mutually exclusive mutations and can present with unique radiographic patterns. Patients with uncommon sites of metastasis may have worse outcomes. Abstract : Supplemental Digital Content is available in the text.